Case Report: Right Insular Stroke Causing Simultaneous Onset of a Functional Vestibular Disorder and Psychiatric Disorder—Persistent Postural–Perceptual Dizziness and Post–stroke Depression - Fipps, David C.; Staab, Jeffrey P.; Allen, Nicholas D. (Frontiers in Psychiatry, 2022)
Introduction: Persistent postural-perceptual dizziness (PPPD) is a chronic functional vestibular disorder that can be precipitated by acquired brain injuries. Post-stroke depression (PSD) is the most common psychiatric sequela of stroke, affecting 33% of stroke survivors. Pathophysiologic mechanisms of PPPD and PSD are not fully understood. Case Report: A 40-year-old female developed new, debilitating chronic dizziness exacerbated by her own motion and exposure to visual motion stimuli plus prolonged depressive symptoms, both beginning within days after a localized right insular stroke. A collaborative evaluation by specialists in neurology, otorhinolaryngology, optometry and psychiatry concluded that the insular stroke caused simultaneous onset of PPPD and PSD. Discussion: Prior case reports described short-lived vertigo following insular strokes, but no long-term vestibular symptoms without ongoing nystagmus or gait ataxia. In this case, chronic dizziness and motion sensitivity continued in the absence of focal neurologic deficits, invoking the possibility that changes in functioning of brain networks subserving spatial orientation persisted despite otherwise adequate recovery from the stroke, a mechanism previously proposed for PPPD. This case also reinforced prior work implicating pathways through the insula in PSD. Co-occurrence of PPPD and PSD offers insights into simultaneous functions of the insula in multiple networks in human brain.